2020
DOI: 10.1186/s13018-020-01891-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bone morphogenetic protein-2/hydroxyapatite on ankle fusion with bone defect in a rabbit model: a pilot study

Abstract: Background: Revision ankle-fusion surgery after a failure of total ankle arthroplasty has a problem with bone-defect management by implant removal. For the reconstruction of bone defects, autogenous bone often causes minor and major complications. Recombinant human-bone morphogenetic protein-2 (rhBMP-2) plays essential roles in bone regeneration strategies, and hydroxyapatite (HA) is beneficial as the rhBMP-2 carrier. In this study, we evaluate whether rhBMP-2/HA can replace autogenous bone in a rabbit ankle-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…11,20,23,54 Previous work showed that rhBMP-2 released from HA is bioactive and that the slower degradation speed of HA may contribute to the sustained release of rhBMP-2. 13,14 By directly reaching the bone marrow's regeneration components and infiltrating the subchondral bone from within the defect, MF promotes cartilage repair. The overlying cartilage is supported and maintained by the subchondral bone, which also interacts with the articular cartilage to transmit biochemical signals via transport pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,20,23,54 Previous work showed that rhBMP-2 released from HA is bioactive and that the slower degradation speed of HA may contribute to the sustained release of rhBMP-2. 13,14 By directly reaching the bone marrow's regeneration components and infiltrating the subchondral bone from within the defect, MF promotes cartilage repair. The overlying cartilage is supported and maintained by the subchondral bone, which also interacts with the articular cartilage to transmit biochemical signals via transport pathways.…”
Section: Discussionmentioning
confidence: 99%
“…11,20,23,54 Previous work showed that rhBMP-2 released from HA is bioactive and that the slower degradation speed of HA may contribute to the sustained release of rhBMP-2. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…4, 16 In the first published study, a dosage of 150-200 g dramatically accelerated bone growth in 5-mm femoral bone defects. 17 Clinical use of BMPs in craniofacial defect cases has been described in a recent study. Chenard et al described the use of BMP-2 to restore various craniofacial abnormalities such as Apert and Crouzon syndrome.…”
Section: Bmp-2 Involvement In Osteogenesismentioning
confidence: 99%